IDENTIFICATION OF SINGLE NUCLEOTIDE POLYMORPHISM INSULIN-LIKE GROWTH FACTOR TYPE 1 GENE IN VERTICAL MANDIBULAR ASYMMETRY PATIENTS WITH IDIOPATHIC SCOLIOSIS SYMPTOM - Sofyanti, Ervina; Siregar, Dewi Indah Sari; Siregar, Otman; Boel, Trelia; Satria, Denny; Tann, Gino (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective:Previous studies reported IGF-1 (Insulin-like Growth factor type-1) gene expression in mandibular condylar cartilage and idiopathic scoliosis development. This paper aims to correlate the Single Nucleotide Polymorphism (SNPs) of IGF-1 gene rs5742632 in vertical mandibular asymmetry patients with idiopathic scoliosis symptom. Methods:TheIGF-1 gene rs5742632 polymorphism of 49 patients (19.38Â±3.24-year-old) who were treated at orthodontics department Dental Hospital Universitas Sumatera Utara and orthopedics department of Haji Adam Malik Hospital from April-August 2017, were genotyped using polymerase chain reaction-restriction fragment length polymorphism analysis in case-control of idiopathic scoliosis symptom. An enzyme-linked immunochemiluminescent assay measured IGF-1 levels. Analyzing of mandibular asymmetry index based on Kjellberg's technique using the panoramic radiograph. Results:The scoliosis symptom based on clinical judgment of orthopedics by asymmetry trunk posture and adam'sforward bend test movement analysis. This study showed no significant difference (p>0.05) in the genotype distribution (rs5742632) haplotype in vertical mandibular asymmetry based on scoliosis symptom. However, there was a significant difference between early and late adolescent among those subjects in IGF-1 level measurement (p=0.033). dam's forward bend test and a scoliometer measurement Conclusion:The result was still not conclusive due to variance in mandibular growth and curve lateral spine in adolescent patients. Further study will requiresubject increment and more specific samples to study the risk factor of vertical mandibular asymmetry .